BRICS AND DEVELOPING COUNTRIES LEGAL EXPERTS FORUM: EMERGENCE OF INTERNATIONAL COORDINATION IN ECONOMIC AND TAX LAW - D. Vinnitskiy (BRICS Law Journal)
BRICS and Developing Countries Legal Experts Forum: Emergence of International Coordination in Economic and Tax Law.